Green Light! : Men of the 81st Troop Carrier Squadron Tell Their Story - Wolfe, Martin (University of Pennsylvania Press, 2016)
In Green Light! Martin Wolfe gives us the big picture of World War II airborne warfare in Europe through the lens of one unit. Wolfe's firsthand account is an engaging and informative narrative that goes beyond the facts to investigate the feelings of the tightly knit unit.